WORLD EXPERIENCE OF GOVERNANCE REFORM - O. V. Gaman Golutvina (Vestnik MGIMO-Universiteta)
The article is devoted to the changes in the configuration of the modern state. The author analyzes the world and domestic experience in the governance reform, determining the content, the main direction, reform technology. The article concerns the theoretical models that have become the basis of governance reform. An informative and functional aspects of governance reforms are considered in the context of modern approaches to the state functions. Considering the results of the governance reform, it should be taken into account that the implementation of these reforms was accompanied by a number of costs. In this regard, a number of experts, including experts from the World Bank, who prepared the materials for the Government Commission on lessons learned from reforms NPM, present restrained assessment of the reform results in various countries, noting their ambiguity and limited scope in relation to the objectives. "Undoubtedly, there are many examples of concrete improvements in certain specific services or in ministries and other organizations in each specific case. However, data on the overall impact of the reforms is very little ... Generally there is no accurate data on the actual results achieved by the majority of implemented reforms... In many cases ... there is difference of opinion about the results of the reform programs "[6, p. 74-75, 36, 40, 47, 78, 82-83, 92].